ODDZIAŁYWANIE KORPORACJI TRANSNARODOWYCH NA PRZEDSIĘBIORSTWA KRAJOWE - PRZYKŁAD PAŃSTW EUROPY ŚRODKOWEJ I WSCHODNIEJ - Fojutowski, Łukasz (Wydział Prawa i Administracji UAM, 2006)
Transnational corporations are often considered as catalysts for economic development. Consequently many countries offer generous incentive packages to attract their investments. The presence of foreign investors in a host country results in a number of complex social and economic effects. This paper aims to analyse the influence of foreign multinationals on local firms. Having first summarised the theoretical background, the author presents the empirical evidence from Poland, the Czech Republic, Slovakia, Estonia, Latvia, Lithuania and the Ukraine. Two channels of that influence can be derived from the literature: linkages and spillover effects. Regarding empirical implementation, it can be stated that contrary to the expectations the influence is not always positive and it varies according to the size of technology gaps and absorptive capacity, corporate strategies, characteristics of industry and local market, and other still not well-known conditions.
INFLUENCE OF MULTINATIONAL CORPORATIONS ON LOCAL COMPANIES: AN EXAMPLE FROM THE COUNTRIES OF CENTRAL AND EASTERN EUROPE